Comparative Evaluation of HETP in Ethanol–Water Distillation Using the Fenske and McCabe–Thiele Methods under Ideal and Non-Ideal Conditions - Hendrini Pujiastuti; Sarah Rafidah; Heri Heriyanto; Nufus Kanani; Vitro Rahmat; Claudia Shinta Wibowo; Haroki Madani (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2026)
Height Equivalent to a Theoretical Plate (HETP) is widely used to assess mass-transfer performance in packed distillation columns by expressing the packing height needed to provide the separation effect of one ideal stage. Therefore, reliable HETP estimation is important for interpreting column efficiency and for supporting distillation-column design and evaluation.. This study evaluates HETP determination in an ethanol–water distillation system using three approaches, namely the Fenske method, and the McCabe–Thiele method under ideal and non-ideal conditions. The experiment was conducted under total reflux to obtain minimum theoretical stages, while ethanol composition in the feed, distillate, and residue was determined from a standard curve relating corrected refractive index to ethanol mole fraction. The feed was prepared from equal volumes of ethanol and distilled water, each 150 mL. The calibration data were represented by a polynomial equation with R² = 0.997. From this relationship, the ethanol mole fractions were estimated as 0.1949 in the feed, 0.3339 in the distillate, and 0.1588 in the residue.. Using these composition values, the Fenske calculation gave 1.1775 theoretical stages with an HETP of 281.7535 cm/plate. The ideal McCabe-Thiele construction resulted in 1.0501 stages and an HETP of 998.8858 cm/plate, whereas the non-ideal McCabe-Thiele construction produced 0.3894 stages and a negative HETP value of -81.8839 cm/plate..These discrepancies indicate that HETP determination is highly sensitive to the selected stage-estimation model and to the reliability of experimental composition data, particularly when refractive-index-based residue measurements are used. The physically unrealistic negative HETP obtained from the non-ideal McCabe–Thiele approach further emphasizes the need for critical evaluation of model assumptions and experimental uncertainty when interpreting HETP values for laboratory-scale ethanol–water distillation.